Benzyl 2-{[2,8-bis(trifluoromethyl)-quinolin-4-yl](hydroxy)methyl}-piperidi ne-1-carboxylate - de Souza, M.V.N.; Goncalves, R.S.B.; Wardell, J.L.; Wardell, S.M.S.V.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The title molecule, C(25)H(22)F(6)N(2)O(3), adopts an open conformation whereby the quinoline and carboxylate ester groups are orientated in opposite directions but to the same side of the piperidine ring so that the molecule has an approximate U-shape. The piperidine ring adopts a distorted boat conformation. In the crystal, inversion dimers linked by pairs of O-H center dot center dot center dot O hydrogen bonds generate R(2)(2)(14) loops.